PERAN PENGAWAS DALAM MEREKONSTRUKSI PENDIDIKAN ISLAM - Harinurdi, Harinurdi (Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2016)
Islamic education is a comprehensive educational and integrative. All the components required to perform its role of Islamic education Islamic education in order to be successful. An Islamic education supervisors to perform its role to the starting point in Islamic values. In the implementation, there are several techniques of Islamic education supervisors who do supervisors. Supervisory duties fostering Islamic education teachers to be able to have a religious type of integration, by modeling or by uswah hasanah, so teachers are also imitating doing the same thing. Supervisors are able to perform its role is always to know and monitor the conditions and the competence of teachers who supervised.Pendidikan Islam merupakan pendidikan yang komprehensif dan integratif. Seluruh komponen pendidikan Islam wajib menjalankan perannya supaya pendidikan Islam tersebut berhasil. Seorang pengawas pendidikan Islam menjalankan perannya dengan bertitik tolak pada nilai-nilai keislaman. Dalam implementasinya, terdapat beberapa teknik supervisi pendidikan Islam yang dapat dilakukan pengawas. Pengawas pendidikan Islam tugasnya membina guru supaya mampu mempunyai tipe yang religius integration, dengan cara modelling atau dengan uswah hasanah, supaya guru juga meniru melakukan hal yang sama. Pengawas yang mampu menjalankan perannya selalu mengetahui dan memantau kondisi dan kompetensi guru yang diawasi.